(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: This study aimed to identify, in the literature, noninvasive measures for the prevention of venous ulcer recurrence (VUs). Methods: An integrative review was carried out in the databases of the Biblioteca Virtual em Saúde (BVS), Public Medline (PubMed), Cumulative Index of Nursing and Allied Health Literature (CINAHL) and Excerpta Medica Database (Embase) in the period from 2015 to 2017. the search was performed using the controlled descriptors «varicose ulcer» and «recurrence» and the Boolean operator AND between them in all databases described, in Portuguese, English, and Spanish. After the searches, two reviewers carried out the pre-selection by titles and a summary of the articles followed by the full reading of the pre-selected studies. Results: 210 studies were identified, of which 188 were excluded because they did not attend to the guiding question. Two reviewers read in full the 22 pre-selected articles and included in this review nine that were part of the discussion of this paper. Conclusion: Studies in this review suggest that adherence and correct use of compressive therapy with socks associated with education and self-care measures are effective in preventing recurrence of VU. The association of acetylsalicylic acid with standard measures of treatment still lacks conclusive results and new studies to prove efficacy are suggested.